Height determination using GPS data, local geoid and global geopotential models - Abdullah, Khairul Anuar (1995)
Orthometric heights are normally derived using the spirit levelling. This requires the spirit level equipment to be set up from point 10 point along a levelling line which is a time consuming and tedious task. GPS offers a new altematiV)O in orthometric height determination very accurately over a comparatively short period. The ellipsoidal height derived from GPS technique can be transformed into orthometric height if we know the geoidal height normally derived from a gravimetric geoid of the area. Unfortunately, we have yet to compute an accurate gravimetric geoid for such purpose, largely due to nonexistence of gravity data for a larger part of the Country. As an alternative, a study was undertaken to look into the feasibility of using a simple local geoid solution and a global geopotential geoid model solution The data used in this study consist of GPS data and known orthometric height ofseveral GPS points. This paper present some of the results obtained so far in estimating orthometric height from GPS data in local en,ironment.